Islamic-Kurdish identity in the face of the hegemony of imported Islamic identity From the perspective of sociological thinkers of religion - Rahim, Hiwa Musa (Sulaimani Journal for Humanities, 2025)
The identity of Kurdish Islam in front of the hegemony of the identity of imported Islam Kurds are one of the oldest nations in the middles east. as zagros people, they have a rich culture of thought and methodology. This identity has left its mark on Islam, so that with the advent of Islam to Kurdistan, the Kurds have not lost their identity. On the contrary they have created a form of Islam is different from the Arabs, Persian Turk and other Muslim nations. Which we call Kurdish Islam in this study In this regard, this study aims to investigate Kurdish Islam based on the sociological theory of religion. Furthermore, this study aims to discuss the dangers that imported Islam foreign Islam seeks to dominate over Kurdish Islam based on the theory of occupation /power and hegemony. Based on the method of sociology of religion, Foucault’s methods of power and occupation and Gramsci’s methods theory of hegemony, this study criticizes the orthodox Islamic view that political Islam and salafism what exists in Islamic societies, so we can find and mention the Islamic –Kurdish forms in the morality and values of Kurdish Muslims. But the both [olitical islamic ideology and salafism intend to import Islamic hegemony over Kurdish Islam and erase all the phenomena and principles that the Kurdish Islam and Kurdish Islamic identity have manifested them in.In the introduction of this research, the frameworks and parts of this research are discussed. In the methods of this research, the sociology of religion and other methods that have helped in the discovery and introduction of Kurdish Kurdish Islam are presented. In its chapters, this study examines the phenomena of religion and identity, the relationship between religion and identity, and then discusses Kurdish Islamic identity. This concept can be explained scientifically. In the second chapter, imported Islam is explained as a new concept and the dangers of this form religion for Kurdish society are mentioned and confirmed. In the final section of the recommendations, we give our recommendations as a solution to the problem
Keywords: Islam; Islamic Kurdish Islamic Culture; Identity; Political Islam; Salafism; Islamic Philosophy; Sufism; Power and Hegemony